2020
DOI: 10.1186/s12895-020-00113-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of cis-acting expression quantitative trait loci in human scalp hair follicles

Abstract: Background The association of molecular phenotypes, such as gene transcript levels, with human common genetic variation can help to improve our understanding of interindividual variability of tissue-specific gene regulation and its implications for disease. Methods With the aim to capture the spectrum of biological processes affected by regulatory common genetic variants (minor allele frequency ≥ 1%) in healthy hair follicles (HFs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It also remains to be seen whether PADI3 mutations can affect the hair follicle in more ways than altering IRS desquamation. For example, Herrera-Rivero et al 7 recently found evidence confirming the contributions of PADI3 to human variation in other hair traits.…”
mentioning
confidence: 89%
“…It also remains to be seen whether PADI3 mutations can affect the hair follicle in more ways than altering IRS desquamation. For example, Herrera-Rivero et al 7 recently found evidence confirming the contributions of PADI3 to human variation in other hair traits.…”
mentioning
confidence: 89%
“…6, Supplementary Data 3). Comparison with an in-house data set on human hair follicle expression 22 revealed that all five MPHL-associated genes (EDA2R, HEPH, CEPT1, WNT10A, EIF3F) are expressed in human hair follicles. Of these, EDA2R, HEPH and WNT10A are located at previously implicated MPHL-GWAS risk loci.…”
Section: Gene-based Association Analysesmentioning
confidence: 99%
“…Here, we investigate the use of noninvasive biospecimens to overcome these barriers. Early studies suggest buccal swabs, hair follicles, nasal swabs, saliva, and urine cell pellets may have potential use in clinical settings and for discovery [ 28 38 ], though no studies to date have comprehensively delineated sources of technical and biological variance in noninvasive tissue types, nor their performance across a wide array of transcriptomic and clinical analyses. Furthermore, no comparisons to invasive sample types have been made in terms of cell type composition or regulation of gene expression and splicing.…”
Section: Introductionmentioning
confidence: 99%